Aga Khan IV and Contemporary Isma‘ili Identity: Pluralist Vision and Rooted Cosmopolitanism - Sahir Dewji (Religions, 2022)
Cosmopolitan engagement and pluralism are consistent themes that run through the Isma‘ili community’s history and continue to be an integral characteristic of the community’s identity. The present Isma‘ili Imam, Karim Aga Khan IV, has been lauded as a champion of pluralism and recognized for his commitment to cosmopolitan ethics which feature prominently in his discourses to both Isma‘ili adherents and other communities. Although the Isma‘ilis have faced vilification and massacres in the course of history, this Muslim minority community has come to be recognized for its endeavors in the area of pluralism and bridge-building under the leadership of Aga Khan IV. The Imam offers religious and worldly guidance from his residence in France, where he has established a Secretariat that includes a number of departments that steer the various communal (jama‘ati) institutions as well as his non-denominational Aga Khan Development Network (AKDN). This non-denominational organization established by Aga Khan IV has emerged as a world leading non-governmental organization providing a number of programs toward improving the quality of life of Muslims and others across the globe. Through his institutions, Aga Khan IV stresses the need for a healthy pluralism that is supported by dialogue and engagement with diversity. One such institution is the Global Centre for Pluralism based in Ottawa, Canada—an international research institution whose activities are underpinned by the Imam’s ethico-religious interpretation of the Islamic faith and commitment to civil society. Aga Khan IV’s discourse of pluralism and cosmopolitan ethics has placed his community at the forefront of engagement with an increasingly diverse world.